2020
DOI: 10.1177/1934578x20915034
|View full text |Cite
|
Sign up to set email alerts
|

The First Report on Chemical Composition and Antimicrobial Activity of Artemisia scoparia Waldst. et Kit. Extracts

Abstract: Volatiles of diethyl ether extract (DE), ethyl acetate extract (EE), and hexane extract (HE) of Artemisia scoparia Waldst. et Kit. were analyzed by gas chromatography with flame ionization detector and gas chromatography-mass spectrometry. In both DE and EE, the main compound was scoparone (24.0% and 86.1%, respectively) while in the HE, alkanes were dominant with nonacosane as the most represented (19.4%). Antimicrobial activity was tested against 4 bacterial strains and 1 fungal strain using disc-diffusion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The linear growth and control linear growth were effectively measured for calculating the percentage inhibition of EOs against the tested fungal strains ( Figure 3 ). The results are consistent with the reported antifungal effects of EOs of A. judaica, A. absintium and A. biennis against Aspergillus niger , however, no reports have been documented on the antifungal activity of A. scoparia EO against A. flavus so far [ 45 ]. Strong antifungal effects have been documented in the literature for Artemisia essential oils along with their cytotoxic, antihepatotoxic and antimalarial activities [ 46 , 47 ].…”
Section: Resultssupporting
confidence: 91%
“…The linear growth and control linear growth were effectively measured for calculating the percentage inhibition of EOs against the tested fungal strains ( Figure 3 ). The results are consistent with the reported antifungal effects of EOs of A. judaica, A. absintium and A. biennis against Aspergillus niger , however, no reports have been documented on the antifungal activity of A. scoparia EO against A. flavus so far [ 45 ]. Strong antifungal effects have been documented in the literature for Artemisia essential oils along with their cytotoxic, antihepatotoxic and antimalarial activities [ 46 , 47 ].…”
Section: Resultssupporting
confidence: 91%
“…[1,2] In some Asian countries, A. scoparia can be used as both traditional medicine and an edible wild vegetable. [3][4][5][6][7] The dried aerial parts of this plant have long been used to treat fever, inflammation, jaundice, and infection. [8] Previous studies showed that the extracts and components had a wide range of pharmaceutical activities such as anti-inflammatory, antibacterial, anticancer, antioxidant, liver protection, antiviral, antiatherogenic as well as neuroprotective functions.…”
Section: Introductionmentioning
confidence: 99%
“…Artemisia scoparia Waldst.et Kit is a perennial herbaceous rhizome and aromatic plant in the composite family, which grows widely in Western Asia and Central Europe [1,2] . In some Asian countries, A. scoparia can be used as both traditional medicine and an edible wild vegetable [3–7] . The dried aerial parts of this plant have long been used to treat fever, inflammation, jaundice, and infection [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Leaves and flowers of A. scoparia are referred in traditional medicine sources with activities such as diuretic, antiphlogistic and for treatment of hepatitis [16]. In addition, several studies reported antioxidant, insecticidal, phytotoxic and anti-inflammatory properties of A. scoparia as well as chemical constituents derived from it such as essential oils, flavonoids and coumarins [16][17][18]. Besides, the family Asteraceae which contains A. scoparia, includes many species where promising antioxidant molecules, especially sesquiterpene lactones were isolated [19].…”
Section: Introductionmentioning
confidence: 99%